The Influence of Morality, Organizational Commitment, and Appropriate Compensation on the Intention of Fraud Study on Public Services in the Investment Sector at the Office of Investment and One Stop Integrated Services (DPMPTSP) of North Sulawesi Province I - Sutrisno, Ellen R.; Tewal, Bernhard; Lengkong, Victor P.K.; Sendow, Greis (Archives of Business Research, 2021)
The objective of this research is to observe the factors that influence the intention to commit fraud in the process of public service investment by focusing on the variables of morality, organizational commitment, and suitability of compensation as dependent variables and intention to commit fraud as independent variable. The study was conducted at the Investment and One Stop Service Office North Sulawesi Province by using quantitative methodology. Data was collected using a questionnaire and then processed by linear regression analysis. The research results showed that morality, organizational commitment and compliance compensation have a negative effect on the intention to commit fraud in the field of public service investment process in the Department of Investment and the One Stop Service Office North Sulawesi Province.